PEMODELAN POLA KOLONISASI VEGETASI PADA EKOSISTEM EKSTREM KAWAH GUNUNG BERAPI RINJANI DAN TAMBORA - Andriwibowo Andriwibowo (UIN Sunan Gunung Djati Bandung, 2021)
Vegetation colonization can occur in various ecosystems. One of the extreme ecosystems for vegetation colonization is a volcanic crater. Given that the ecosystem is located at an altitude of thousands of meters, sometimes high temperatures, strong winds, and no soil layer that contains nutrients. Even so, in the vegetation ecosystem there are sediment deposits and sometimes a lake is formed. Sediment deposits on the surface of the crater will be a medium that supports vegetation colonization. Related to this, this study aims to model the colonization of vegetation around the crater formed at Rinjani (3726 m) and Tambora (2850 m) volcanoes. The crater of Mount Rinjani is known to have formed sedimentation on the surface of the crater covering an area of 3.983 km2. In the sediment the vegetation cover is estimated at 2.866 km2. New vegetation colonization appears to have formed on the edge of the crater surface on the south side. While the area of sediment deposits in the crater of Mount Tambora is 5.333 km2. In the sediment the vegetation cover is estimated at 2.188 km2. In the Tambora crater, new vegetation colonization was also seen around the crater surface. The vegetation colonization index in Rinjani is 0.719 and is greater than the index in Tambora with a value of 0.410. It can be concluded that the vegetation colonization on the surface of the crater is higher at Mount Rinjani.